Medical Cannabis Use Among Canadian Veterans and Non-Veterans: A National Survey - Gunel Valikhanova; Yuka Kato; Mary-Ann Fitzcharles; Mark Ware; Deborah Da Costa; Ilka Lowensteyn; Ho Sum Cheung; Steven Grover (Mary Ann Liebert, 2023)
Background: Medical cannabis (MC) is used by Canadian Veterans to manage a wide range of health issues. However, there is little information comparing the reasons for MC use and its perceived effectiveness between Veterans and non-Veterans. Objects: We compared MC use among a convenience sample of Canadian Veterans and with non-Veteran controls, including demographics, reasons and patterns of use, and perceived effectiveness. Methods: Between November and December 2021, Canadian Veterans using cannabis were invited to participate in a survey using a national press release, social media, and announcements on online platform dedicated to promoting health among Canadian Veterans and non-Veterans during the pandemic (www.MissionVav.com). The survey was also mentioned in a monthly newsletter from Veteran Affairs Canada. Self-reported effectiveness was evaluated using a 0 to 10 visual analogue scale (0 being not all effective, 10 being the most effective). Results: The survey was completed by 157 people, including 108 (69%) males and 49 (31%) females. The mean age was 57 years (range 19 to 84). Among responders, 90 (63%) identified as Veterans. The most common reasons for MC use among Veterans included: insomnia (80%), anxiety (73%), and depression (52%). Veterans reported medical conditions such as chronic pain (88%) and arthritis (51%). Compared with non-Veterans, Veterans were significantly more likely to be male (83% vs. 49%), have a higher BMI (35.2 vs. 30.9), to report problems with sleep, anxiety, depression, and PTSD, and to use cannabis in edible form (51% vs. 22%). Self-reported mean effectiveness scores for MC were highest for PTSD (8.4), insomnia (8.2), anxiety (8.1), depression (8.0), and chronic pain (7.6). Conclusions: We found important differences in user characteristics and cannabis use patterns between Canadian Veterans and non-Veterans. Further controlled studies are required to validate these findings, but these data suggest that orally administered cannabis products may be worth further study.